2011
DOI: 10.1016/j.ijgo.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of urinary incontinence among female athletes

Abstract: Urinary incontinence is a prevalent condition among athletes that is not openly discussed. However, it causes regular changes in their physical performance and daily life. More research is needed to increase awareness of UI and to design interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
8
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 18 publications
8
82
8
12
Order By: Relevance
“…One study found that due to SUI, 10 % of women cease participation in their favourite sport and a further 20 % alter their participation to reduce leakage episodes [9]. Common preventative strategies that women use to reduce leakage during exercise are known to include limiting fluid intake; voiding prior to exercise; use of pads and modification of activity, often with the selection of lower-impact options [8][9][10]12].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that due to SUI, 10 % of women cease participation in their favourite sport and a further 20 % alter their participation to reduce leakage episodes [9]. Common preventative strategies that women use to reduce leakage during exercise are known to include limiting fluid intake; voiding prior to exercise; use of pads and modification of activity, often with the selection of lower-impact options [8][9][10]12].…”
Section: Introductionmentioning
confidence: 99%
“…3 However, a recent study of SUI in young nulliparous athletes showed a prevalence of 36.4%. 4 Some studies have shown that the high prevalence of SUI in nulliparous athletes is associated with the type of sport. A systematic review conducted in 2004, 2 revealed that the prevalence of UI during sports practice varied between 0% (golf) and 80% (trampoline).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence is associated with medical and psychological morbidity that greatly influences the quality of life, and has a negative impact on athletic performance 10. Medically, it can be associated with perineal candida infections, cellulitis, pressure ulcers, urinary tract infections, sleep disturbances and even higher risk of falls and fractures 15 16.…”
Section: Introductionmentioning
confidence: 99%